Exploring transformational adaptation strategy through rice policy reform in the Philippines - Pradesha, Angga; Robinson, Sherman; Rosegrant, Mark W.; Perez, Nicostrato D.; Thomas, Timothy S. (International Food Policy Research Institute, 2019)
The Philippines is much more prone to climate change effects than are many other countries. The potential impact on the agriculture sector is of particular concern, given its vital role in the economy and for vulnerable households. Most research warns of the negative impact of climate change on yields for major cereal crops, which could threaten food security and hinder the long-run development process. Incremental adaptation through the introduction of new crop varieties, improved agricultural management practices, and more efficient irrigation are expected to reduce yield losses. However, efforts to promote systemwide adjustment would have broader effects, especially as the risk of climate change increases. This study proposes a new approach for adaptation strategies by exploring policy reform in agriculture as a transformative way to help economic agents adapt to climate change. We specifically explore the rice policy reform currently being pursued by the government through the abolishment of the rice quota program. We find this reform could help transform the agricultural and economic system by allowing scarce resources move from low- to high-productivity sectors, thus increasing the country’s adaptive capacity. However, the rice farmer and vulnerable groups that are prone to climate shocks are adversely affected by the policy. Thus, we introduce alternative intervention policies to complement the reform agenda by providing a cash transfers program to vulnerable groups or a subsidy to support rice farmers. Both offer less impact in economic efficiency gains, but the cash transfer program is superior in terms of supporting the vulnerable group in coping with climate change under the rice reform policy. This shows that the transformational adaptation strategy may create a welfare loss to certain agents but that adding government intervention could act as the second-best policy and become a transition pathway before the whole system transforms to reach the optimal efficiency point when the intervention program is eventually phased out.